2021
DOI: 10.1038/s41586-021-03350-4
|View full text |Cite
|
Sign up to set email alerts
|

DPP9 sequesters the C terminus of NLRP1 to repress inflammasome activation

Abstract: NLRP1 is a cytosolic inflammasome sensor that mediates activation of caspase-1, which in turn induces cytokine maturation and pyroptotic cell death 1-6 . Gain-of-function NLPR1 mutations cause skin inflammatory diseases including carcinoma, keratosis, and papillomatosis 7-14 . NLRP1 contains a unique function-to-find domain (FIIND) that autoproteolyzes into noncovalently associated subdomains [15][16][17][18] . Proteasomal degradation of the autoinhibitory N-terminal fragment (NT) activates NLRP1 by releasing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
159
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(172 citation statements)
references
References 56 publications
11
159
0
2
Order By: Relevance
“…Hollingsworth et al indicated that cytosolic dipeptidyl peptidase 9 (DDP9) interacts with full-length NLRP1 and NLRP1 CT to form a ternary complex, which sequesters NLRP1 CT and inhibits inflammation. Conversely, the inhibitory effect is rescued by Val-boroPro (VbP), an inhibitor of DPP8/DPP9 132 .…”
Section: Correlation Between Pyroptosis and Modulation Of Cancer Immunitymentioning
confidence: 99%
“…Hollingsworth et al indicated that cytosolic dipeptidyl peptidase 9 (DDP9) interacts with full-length NLRP1 and NLRP1 CT to form a ternary complex, which sequesters NLRP1 CT and inhibits inflammation. Conversely, the inhibitory effect is rescued by Val-boroPro (VbP), an inhibitor of DPP8/DPP9 132 .…”
Section: Correlation Between Pyroptosis and Modulation Of Cancer Immunitymentioning
confidence: 99%
“…The proteasome-mediated degradation of the NT fragments releases the CT fragments from autoinhibition ( 4, 5) . Initially, each freed CT fragment is restrained in a ternary complex with one copy of the full-length (FL) sensor protein (NLRP1 or CARD8) and one copy of either dipeptidyl peptidase 8 or 9 (DPP8/9) ( 6, 7 ). However, if enough CT fragments are released or if the ternary complex is disrupted by DPP8/9-binding ligands, the CT fragments assemble into caspase-1-activating structures called inflammasomes and trigger pyroptosis.…”
Section: Main Textmentioning
confidence: 99%
“…dsRNA directly interacts with the NACHT-LRR region, triggering ATP hydrolysis, and presumably NT degradation and CT release, via unknown mechanisms. DPP8/9 inhibitors, including Val-boroPro (VbP), both accelerate the proteasome-mediated degradation of the NT fragment through a poorly characterized pathway and destabilize the NLRP1 FL -NLRP1 CT -DPP8/9 repressive ternary complex ( 6, 7, 14, 16, 17 ). Of these three triggers, only DPP8/9 inhibitors also activate the rat and mouse NLRP1 inflammasomes ( 15 ) and the human CARD8 inflammasome (rodents do not express CARD8) ( 13, 18 ).…”
Section: Main Textmentioning
confidence: 99%
“…Knockdown of DPP7 increased apoptosis by upregulating Bax–Bcl2 signaling in the HepG2 liver cancer cell line [ 19 ]. NLR family pyrin domain-containing 1 (NLRP1) can interact with DPP8 and DPP9, which can serve as a checkpoint for activating the NLRP1 inflammasome [ 20 ]. A DPP8 and DPP9 inhibitor can promote apoptosis by activating poly(ADP ribose) polymerase (PARP) and caspase-3 in multiple myelomas [ 21 ].…”
Section: Introductionmentioning
confidence: 99%